Polarization conversion in soft glass fluoride and chalcogenide fibers for mid-infrared applications - Md Moinul Islam Khan; Md Hosne Mobarok Shamim; Jean-Luc Delarosbil; Younes Messaddeq; Frederic Smektala; Martin Rochette (JPhys Photonics)
Mid-infrared (MIR) technologies are crucial for applications from chemical sensing to precision medical surgery. Effective polarization control is essential to enhance the functionality of fiber systems. Current solutions for polarization control in the MIR primarily involve free-space devices and components. In this work, we take a step forward and experimentally demonstrate polarization conversion within soft glass fluoride and chalcogenide fibers using a commercially available in-line polarization controller (PC). Our experiments using a single PC show a polarization extinction ratio (PER) of 20.7 dB in a ZBLAN fiber (FiberLabs) with a coating of urethane acrylic resin. Cascading two PCs enhances the PER to 39.1 dB while reducing the required compressive force and, thus, increasing the fiber lifetime. Chalcogenide fibers (As _2 Se _3 , As _2 S _3 , Ge _20 Se _60 Te _20 ) are coated with polymethyl methacrylate and tested using a single PC. Thanks to the higher strain-optic coefficients of chalcogenide glass, these fibers exhibited exceptional PER values, reaching 39.3 dB for As _2 Se _3 , 41.4 dB for As _2 S _3 , and 38.3 dB for Ge _20 Se _60 Te _20 . The polymer coatings of the ZBLAN and chalcogenide fibers effectively protect them from compressive force and twisting, enabling them to endure more than 30 cycles of compression and decompression without breakage. Stability test conducted over 12 h with ZBLAN fiber demonstrated that the achieved polarization state remains stable, with maximum deviations due to environmental factors estimated to be less than 2%. This work is the first proof that in-line polarization control using soft glass fibers is achievable, paving the way toward the development of all-fiber MIR systems.